The Therapeutic Community: A Unique Social Psychological Approach to the Treatment of Addictions and Related Disorders - De Leon, George; Unterrainer, Human F. (Frontiers in Psychiatry, 2020)
The evolution of the contemporary Therapeutic Community (TC) for addictions over the past 50 years may be characterized as a movement from the marginal to the mainstream of substance abuse treatment and human services. TCs currently serve a wide array of clients and their diverse problems; through advances in research in treatment outcomes, the composition of staff has been reshaped, the duration of residential treatment has been reduced, the treatment goals have been reset and, to a considerable extent, the approach of therapy itself has been modified. An overview of the TC as a distinct social-psychological method for treating addiction and related disorders is provided by this paper. Included in this is a focus on the multifaceted psychological wounds that consistently show a strong association with addiction and thereby require initiating a recovery process characterized by life-style and identity changes.